BARRIERS TO INFECTION PREVENTION AND CONTROL PRACTICE AGAINST COVID-19: A SURVEY OF HEALTHCARE WORKERS IN NIGERIA (Journal of Biomedical Investigation, 2023)
Background: Following the COVID-19 pandemic which was declared a public health emergency all over the world, healthcare workers in Nigeria are still faced with many types of barriers to infection prevention and control practices. The study assessed the barriers to compliance with Infection Prevention and Control (IPC) practices among Healthcare Workers (HCWs) in Nigeria during the early phase of COVID-19.Methodology: A cross-sectional descriptive design using a non-probability purposive sampling technique was used to select seventy-eight (78) HCWs working in different healthcare facilities in Nigeria involving medical and allied health professionals such as nurses/midwives, physiotherapists, radiographers, pharmacists, orthotist, prosthetist, orthopaedic technologists, and public health professionals Analysis of the results was done using known standard methods and the results were statistically analyzed.Results: The findings of the study revealed 78 HCWs participated in this study comprising 44(56.4%) medical doctors, 4(4.1%) Nurses, 17(21.8%) Physiotherapists, 5(6.4%) Laboratory scientists, and 8(10.4%) others. Thirty-nine (50.0%) of the participants found overcrowding/understaffing as one of the major barriers to IPC, 37(47.4%) indicated less commitment of HCWs to the IPC policies and 35(44.9%) indicated lack of water as the major barrier to IPC practice. Limitation of personal protective equipment such as face masks was seen as a barrier to compliance in 17(21.8%) of participants and the unavailability of alcohol-based hand rubs was seen as a barrier by 33(42.3%) of participants.Conclusion: Several factors were identified as constituting varying degrees and levels of barriers to IPC practices following COVID-19 in Nigeria. There is a need for the government, policymakers, the leadership of private healthcare facilities, and Healthcare workers to establish an innovative, effective, and efficient system to address barriers to IPC practices which will help to reduce the risk and spread of COVID-19 in healthcare settings.
Keywords: COVID-19; Infection Prevention and Control; Barriers; Healthcare Workers; Nigeria